Higher aged neutrophils and differential inflammatory profiles in sickle cell disease patients on chronic transfusion therapy versus those on hydroxyurea - Terrigno, Katrina; Flamholz, Zachary N.; Mahant Mahant, Aakash; Agalliu, Ilir; De Los Santos, Jennifer; Ireland, Karen; Keenan, Janine; Kazmi, Jacob S.; Correa, Anayeli; Frenette, Paul S.; Kelly, Libusha; Herold, Betsy C.; et al. (Frontiers in Immunology, 2025)
BackgroundSickle cell disease (SCD) is characterized by a point mutation in the β globin molecule, causing the sickling of red blood cells, and leading to hemolytic anemia, pain, and end-organ damage. Hydroxyurea (HU) is a cornerstone of SCD patient treatment, while chronic transfusions (CT) are used as part of treatment for more severe SCD. Increases in aged neutrophils and inflammation have been linked to more severe SCD and contribute to vaso-occlusive crises. The current study was designed to test the hypothesis that HU reduces inflammation and aged neutrophils.Study designWe compared clinical characteristics, aged neutrophils, levels of select cytokines, chemokines, and cell adhesion molecules in the blood and the Shannon diversity index (SDI) and ratio of Firmicutes/Bacteroides (F:B) in stool samples from pediatric SCD patients treated with HU (n=40) versus CT (n=14).ResultsPatients in the HU group had significantly lower total and aged neutrophils (p<0.0001) compared to the CT group and also had lower levels of several chemokines including CXCL10 (IP-10), CCL2 (MCP-1) and CCL4 (MIP-1β) as well as IFN-γ and IL10. Conversely, HU was associated with higher levels of IL-1α, IL-6 and IL-8. There were no significant differences in cell adhesion markers or in markers of gut microbial dysbiosis between treatment groups. In a multivariable linear regression model, only being on CT was associated with increased number of aged neutrophils (p<0.001) whereas being on CT and having a lower SDI were associated with higher total neutrophil count.DiscussionLower numbers of total and aged neutrophils and lower levels of several cytokines and chemokines in the HU group highlight the drug’s potential to modulate leukocyte activation and recruitment. These findings suggest that adding or maintaining HU therapy in SCD patients undergoing CT could potentially enhance immunologic regulation and warrants further study.